2020
DOI: 10.1002/jmv.26689
|View full text |Cite
|
Sign up to set email alerts
|

No SARS‐CoV‐2 carriage observed in children attending daycare centers during the intial weeks of the epidemic in Belgium

Abstract: To gain knowledge about the role of young children attending daycare in the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) epidemic, a random sample of children ( n = 84) aged between 6 and 30 months attending daycare in Belgium was studied shortly after the start of the epidemic (February 29th) and before the lockdown (March 18th) by performing in‐house SARS‐CoV‐2 real‐time polymerase chain reaction. No asymptomatic carriage of SARS‐CoV‐2 was detected, whereas common cold … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Despite a regional 7-day incidence of 20 to 152 cases per 100 000 population, the frequency of SARS-CoV-2 infections found in DCCs was very low and comparable to other studies. 18 , 19 , 24 , 25 , 26 , 27 During our study, introduction of SARS-CoV-2 into DCCs occurred mainly via adult index cases. This observation supports early vaccination of CCWs, as has been prioritized in many countries including Germany.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Despite a regional 7-day incidence of 20 to 152 cases per 100 000 population, the frequency of SARS-CoV-2 infections found in DCCs was very low and comparable to other studies. 18 , 19 , 24 , 25 , 26 , 27 During our study, introduction of SARS-CoV-2 into DCCs occurred mainly via adult index cases. This observation supports early vaccination of CCWs, as has been prioritized in many countries including Germany.…”
Section: Discussionmentioning
confidence: 75%
“…18,19,[24][25][26][27] During our study, introduction of SARS-CoV-2 into DCCs JAMA Network Open | Infectious Diseases SARS…”
mentioning
confidence: 99%
“…The study found no significant differences in SARS-CoV-2 RNA loads between children and adults [ 72 ]. At the same time, another report could not prove SARS-CoV-2 carriage in children attending daycare centres during the initial weeks of the epidemic in Belgium [ 73 ]. Uncertainty over the viral load and secondary attack rate in children prompted views that dramatic public health measures like school closures were not evidence-based, leading to a heated debate over the issue [ 74 - 77 ].…”
Section: Viral Load In Children and Young Peoplementioning
confidence: 99%
“…We identified 21 studies that reported data on SARS-CoV-2 infections in diverse educational settings, from kindergartens and daycares to primary and high schools (eTable 1 in the Supplement), [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] involving more than 120,000 subjects. Fifteen studies were from Europe, 12,13,[15][16][17][19][20][21][22][23][24]27,29,30 five from US, 16,18,25,26,28 one from Israel. 14 Overall, studies documented SARS-CoV-2 positivity rates from the beginning of the pandemic in March 2020 until May 2021, including periods of low and high community transmission.…”
Section: Sars-cov-2 Positivity Rates In Educational Settings (Screening Studies)mentioning
confidence: 99%
“…Fifteen studies reported SARS-CoV-2 point prevalence in a total of 112,131 subjects, [12][13][14][15][16][17][18][19][20][21][22][23][30][31][32] including one study providing data collected during two rounds of testing within the COVID-19 Schools Infection Survey. 23 A total of 326 coronavirus infections were detected.…”
Section: Sars-cov-2 Positivity Rates In Educational Settings (Screening Studies)mentioning
confidence: 99%